Concept of Vector Multicomponent Physical Quantities, Models and Measurement Method - V. N. Nesterov (Приборы и методы измерений, 2022)
The paper presents a new view of vector physical quantities as multicomponent quantities. Each of the components of the mentioned multicomponent quantities can carry important and even unique information about the sources and causes of their occurrence. Looking at the vector quantity as the multicomponent quantity led to the need to form the corresponding conception. There are three positions of this conception in this paper, which are formulated as follows: vector multicomponent physical quantities are considered as functions of the set of their constituent information components; the communication functions of the specified information components in the models of multicomponent physical quantities are determined by the laws of vector algebra; information models of vector multicomponent physical quantities allow an alternative representation of information components depending on the selected coordinate system.The mathematical model of the vector multicomponent physical quantity is presented. This model is fundamental and directly follows from the positions of the conception formulated above. This model can be applied to describe multicomponent displacements and deformations that both simple and complex objects undergo. An example of the complex object can be the manipulator of the universal industrial robot. The space for modeling multicomponent displacements of simple objects was shown in the paper. Information models of vector multicomponent physical quantities allow one to alternatively represent informative components. And the task of constructing such models is complex and ambiguous. Therefore, the formal apparatus for the synthesis of such models, which is based on certain rules and conventions, was proposed in the paper. The theoretical foundations of the method of optical measurements of informative components of multicomponent displacements and deformations of simple objects, which involves the use of multidimensional test objects, are presented.